A study about the impact of the topological arrangement of fibers on fiber-reinforced composites: Some guidelines aiming at the development of new ultra-stiff and ultra-soft metamaterials. (15th October 2020) - Giorgio, Ivan; Ciallella, Alessandro; Scerrato, Daria
Highlights: We propose two particular fiber arrangements with the intention of realizing ultra-stiff and ultra-soft composites. In particular, we also consider the case of curved fibers. We introduce a model for these lattice plates that is able to describe the behavior of an in-plane orthotropic lamina within the framework of the strain-gradient elasticity theory. Numerical simulations have been performed using the finite element method to investigate the mechanical behavior of the considered textures. Abstract: Fiber-reinforced composites are materials that display a great potentiality in many applications for their multifaceted features. The employment of curved fibers contributes to enhancing this already wide range of possibilities further. In this paper, we propose two particular fiber arrangements with the intention of realizing ultra-stiff and ultra-soft composites. For this purpose, we explore the texture based on isostatic lines, which is bio-inspired to obtain a high strength composite and the pantographic pattern, which enables considerable displacement with very low resistance. To model these particular lattice plates, we consider an in-plane orthotropic lamina within the framework of the strain-gradient elasticity theory. Numerical simulations have been performed using the finite element method to investigate the mechanical behavior of the considered textures. A regular straight texture with fibers parallel to the edges of a rectangular sample has been taken into account as reference texture for comparison. Through some tests, we show that for the considered textures, namely the isostatic and the pantographic ones, the displacement force graphs differ by several orders of magnitude, justifying the characterization of their behavior.